Factors promoting collaboration between community sports leaders and guardians in urban areas of Japan: A cross-sectional study - Hosokawa, Yoshino; Yako-Suketomo, Hiroko; Ishii, Kaori; Oka, Koichiro (Frontiers in Public Health, 2022)
Background: Community sports leaders (CSLs) are expected to play an important role in promoting regional sports in Japan. Increased opportunities for CSLs to work in schools and engage with guardians could encourage middle-aged adults to participate in regional sports activities. However, few CSLs work with guardians, and there is no evidence regarding what CSL characteristics encourage collaboration. The present study aimed to ascertain the aspects of coordination for CSLs collaborating with guardians in urban areas. Methods: A self-administered questionnaire survey was mailed to all 1,489 CSLs through 59 municipalities using the CSL out of 62 in Tokyo, Japan, from July to November 2021. The questionnaire covered sociodemographic data, variables related to CSL activities, coordination functions, and experience collaborating with guardians. We conducted a binomial logistic regression analysis using experience collaborating with guardians as the dependent variable, coordination function as the explanatory variable, and gender, age, residence duration, years of CSL experience, and the number of activities as covariates. Results: The analyzed sample comprised 478 CSLs. Binomial logistic regression analysis revealed a significant relationship between experience collaborating with guardians and the coordination function of internal/external CSL organizations, such as participation in non-CSL community activities, experience teaching and supporting their own children’s sports, activity initiatives, number of times they used the school gymnasium, awareness of the regional sports plan, and cooperation with the chairman of the neighborhood association. Conclusions: Collaboration with guardians was related to CSL’s individual experience engaging in regional sports from parenting and community collaboration, such as participation in non-CSL community activities and their relationship with the chairman of the neighborhood association. CSL activities may have the potential to encourage middle-aged adults to participate in regional sports.